2008
DOI: 10.1111/j.1462-5822.2008.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Toxoplasma gondii results in dysregulation of the host cell cycle

Abstract: SummaryMammalian cells infected with Toxoplasma gondii are characterized by a profound reprogramming of gene expression. We examined whether such transcriptional responses were linked to changes in the cell cycle of the host. Human foreskin fibroblasts (HFFs) in the G0/G1 phase of the cell cycle were infected with T. gondii and FACS analysis of DNA content was performed. Cell cycle profiles revealed a promotion into the S phase followed by an arrest towards the G2/M boundary with infection. This response was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
93
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 65 publications
(96 reference statements)
13
93
1
Order By: Relevance
“…Interestingly, many of the Toxoplasma-induced c-Myc targets in our data set have been shown to be positive regulators of cell survival and viability and negative regulators of apoptosis and cell cycling (specifically, genes regulating the G 2 /M checkpoint were enriched [P 檄 0.00132]), which is consistent with previous reports on the regulation of apoptosis and cell cycle by this parasite (43)(44)(45). Altogether, these data suggest that the upregulation of c-Myc in Toxoplasma-infected cells has a substantial impact on the host transcriptome and, likely, the overall phenotype of the infected cell.…”
Section: Toxoplasma Infection Results In Specific Upregulation Of Hossupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, many of the Toxoplasma-induced c-Myc targets in our data set have been shown to be positive regulators of cell survival and viability and negative regulators of apoptosis and cell cycling (specifically, genes regulating the G 2 /M checkpoint were enriched [P 檄 0.00132]), which is consistent with previous reports on the regulation of apoptosis and cell cycle by this parasite (43)(44)(45). Altogether, these data suggest that the upregulation of c-Myc in Toxoplasma-infected cells has a substantial impact on the host transcriptome and, likely, the overall phenotype of the infected cell.…”
Section: Toxoplasma Infection Results In Specific Upregulation Of Hossupporting
confidence: 80%
“…Another possibility is that Toxoplasma co-opts c-Myc to regulate the host cell cycle. Our findings using IPA of gene expression changes in Toxoplasma-infected cells are consistent with previous reports that have shown that Toxoplasma can induce host cell cycle arrest at a G 2 /M checkpoint (43,44). Restricting the proliferation ability of the host cell could be a strategy to ensure that enough nutrients are available for the parasite instead of being utilized by the host cell.…”
Section: Figsupporting
confidence: 79%
“…By stalling host cell division prior to cytokinesis, the parasites may ensure a stable and spacious environment for replication, as offered by a multinucleated cell. To this point, infection of quiescent cells with T. gondii induces an increase in D and E cyclins, thus promoting progression through G 1 and transition into S phase, respectively (90). Therefore, in Toxoplasma-infected cells, there is not only an induction of entry into S phase triggered by the parasite but also an arrest in cell cycle progression in the S/G 2 transition, based on host cyclin expression levels and accumulation in the infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…As cell cycle progression is a fundamentally important biological process that leads to many functional alterations in cells, it is not surprising that numerous intracellular pathogens manipulate the cell cycle progression of their host cells. While important and well-studied examples arise from viral and bacterial infections (reviewed in references 1 and 2), protozoan parasites, such as Toxoplasma gondii (3)(4)(5), Trypanosoma cruzi (6), Eimeria bovis (7), Encephalitozoon spp. (8), and Leishmania major (9), have all been suggested to modulate host cell cycle progression.…”
mentioning
confidence: 99%